Challenging the universality of job resources: why, when, and for whom are they beneficial? - Van Veldhoven, M.; Van den Broeck, A.; Daniels, K.; Bakker, B.A.; Tavares, S. M.; Ogbonnaya, C. (Applied Psychology: An International Review, 2020)
In this paper we introduce the topic of job resources and elaborate on their relevance for research and practice in work psychology. We start out with a brief overview of the historic and current understanding of job resources. Next, we discuss the need for a more nuanced perspective on the effects of job resources and present some ideas on how to move this forward. After these conceptual preliminaries, we introduce the papers in the special issue and conclude with a brief summary of the special issue’s key messages.